Blütenmeere jenseits naturalisierender Literaturgeschichte - Jonas Hock (Recherches Germaniques)
In his book Epochen der italienischen Lyrik (Epochs of Italian Poetry, 1964), Hugo Friedrich presents Mannerism as a clear decline from the previously effective classical principles, thus largely following a paradigm of decline that his Structure of Modern Poetry (1956) seems to oppose. At the same time, journalist Gustav René Hocke published two volumes on Mannerism in art (I) and literature (II) in the series “rowohlts deutsche enzyklopädie”, in which he advocated radically opposite views and presented a cyclical model of art and intellectual history. He promoted nothing less than the salvation of homo europeus by taking up an “irregular”, namely mannerist tradition. In doing so, Hocke—like Friedrich—referred to Ernst Robert Curtius and his distinction between Classicism and Mannerism. The article examines how Hocke’s cyclic conception differs from Friedrich’s understanding of epochs, the links both have to Curtius’s topology and whether the three approaches can be understood as naturalizations of literary history.